Ac-HSP20 Is Associated With the Infectivity and Encystation of Acanthamoeba castellanii - Wang, Ningning; Sun, Hongyu; Liu, Di; Jiang, Xiaoming; Zheng, Meiyu; Zhu, Wenhe; Liu, Quan; Zheng, Wenyu; Feng, Xianmin (Frontiers in Microbiology, 2021)
Acanthamoeba castellanii is a pathogenic and opportunistic free-living amoeba that causes Acanthamoeba keratitis (AK) and granulomatous amebic encephalitis (GAE) in immunocompromised individuals. The biological and pathogenic characterizations behind this opportunistic protozoan is not fully understood. This study aimed to determine the biological functions of Ac-HSP20 involved in the maintenance of life cycle and the infectivity of A. castellanii. Immunoscreening A. castellanii cDNA library with A. castellanii infected rabbit sera identified three positive clones, one of them was a putative heat shock protein (Ac-HSP20). The recombinant 23 kDa Ac-HSP20 protein (rAc-HSP20) was successfully expressed in E. coli BL21 (DE3) and purified using metal affinity chromatography. The rabbits immunized with rAc-HSP20 produced high titer antibody (1:25,600). Immunolocalization with the antibody identified the expression of native Ac-HSP20 on the surface of both A. castellanii trophozoites and cysts. Further Western blot with antibody identified that the expression of native Ac-HSP20 was 7.5 times higher in cysts than in trophozoites. Blocking Ac-HSP20 on the membrane of trophozoites with specific antibody or silencing Ac-hsp20 gene transcription by siRNA inhibited their transformation into cysts at the early stage, but returned to normal at the late stage by stimulating the transcription of Ac-hsp20. Incubation of trophozoites with anti-Ac-HSP20 IgG increased macrophage-involved phagocytosis to the protozoa and inhibited trophozoite infectivity on the cornea of rabbits compared with that without antibody. Our study provides that Ac-HSP20 is a surface antigen involved in the encystation and infectivity of A. castellanii and thus an important target for vaccine and drug development.